RANCANG BANGUN SISTEM PERENDAMAN SESAAT YANG DILENGKAPI DENGAN SENSOR LEVEL - Asrizal Deri Futra; Iwa Tama Putra; Sumantri Kurniawan Risandriya (Politeknik Negeri Batam, 2019)
Temporary Immersion System (TIS) is one of technologies for plant micro propagation that the plant tissue is immersed temporarily. During the immersion period, the liquid medium is flowed from the liquid jar to the tissue jar. After the certain time, the liquid medium will flow to its jar because the medium jars were placed below the culture jars. This immersion system consisted of five liquid medium jars and five tissue jars that integrated to level sensor. The data of immersion time and periods were recorded in micro SD to make sure that the system worked as time set. In the immersion process testing, the air pressures were varied, 1 bar and 1.5 bar to flow water of 254.5 ml from the liquid medium jars to the culture jars. The pressure of 1 bar could drain the liquid medium from its jar to the culture jar and it caused less bubbles than 1.5 bar did. From the data recorded in micro SD, the time and duration of immersion was the same as time input.